2018
DOI: 10.1007/s13205-018-1373-1
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification and expression analysis of superoxide dismutase (SOD) gene family in Medicago truncatula

Abstract: Superoxide dismutase (SOD) proteins are crucial antioxidant enzymes that play critical roles in plant growth, development, and response to various abiotic stresses. The gene family has been characterized in various plant species, but not in yet. Here, a total of 7 genes were first identified from the whole genome of, including 1 , 2, and 4 /, which are unevenly distributed in five out of the eight chromosomes. Phylogenetic analysis showed that SOD proteins from and other plant species could be classified into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 36 publications
9
35
0
Order By: Relevance
“…However, Cu/ZnSODs subfamily genes possessed seven to eight exons. These results are in line with previous reports (Song et al, 2018), and further confirmed that three subfamilies may displayed a great diversity in soybean. Thirdly, the conserved motifs further revealed the varied widely from different subfamilies, especially MnSODs and Cu/ZnSODs subfamily (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, Cu/ZnSODs subfamily genes possessed seven to eight exons. These results are in line with previous reports (Song et al, 2018), and further confirmed that three subfamilies may displayed a great diversity in soybean. Thirdly, the conserved motifs further revealed the varied widely from different subfamilies, especially MnSODs and Cu/ZnSODs subfamily (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas, almost all the expression levels of soybean SOD genes displayed no significant change under cold stress, except for a slightly up-regulation (|Log 2 fold change| > 1) of GmFSD2. This indicated that the soybean SOD genes may play different roles under cold stress, which also consistent with previous research (Song et al, 2018). In addition, we also examined the expression patterns of soybean SOD genes under water-deficit stress (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, AOS was also encoded by a single gene, but the HPL genes existed in multiple copies. According to the criteria in a previous report [27], two tandem duplication events and one segmental duplication event were identified (Figure 1). A previous study showed that a single amino acid exchange leads to the conversion of an AOS to an HPL [43].…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular localization of the watermelon CYP74 proteins was predicted using ProtComp 9.0 (http://linux1.softberry.com/). The chromosomal locations of watermelon CYP74 genes were obtained from watermelon (97103) v1 genome database, and the segmental and tandem duplications were checked based on the methodology in a previous study [27]. To identify the putative cis-acting regulatory elements of the promoter regions of watermelon CYP74 genes, the 1,500-bp sequences upstream the start codon of watermelon CYP74 genes were retrieved and analyzed using PlantCARE tool (http://bioinformatics.psb.ugent.be/webtools/plantcare/html/).…”
Section: Protein Properties Chromosomal Locations and Promoter Analmentioning
confidence: 99%
“…Another SOD, nickel superoxide dismutase (NiSOD), has not been found in plants (Dupont et al, 2008). For the three main types of SODs identified in plants, Cu/ZnSOD is the most abundant, and is mainly distributed in the chloroplasts, plants cytoplasm, peroxisomes, and/or the extracellular space (Song et al, 2018). FeSOD is considered the oldest type of SOD, and is mainly localized in the chloroplast with a few proteins found in the cytoplasm, whereas MnSOD typically has a mitochondrial localization (Pan et al, 2019;Perry et al, 2010).…”
Section: Introductionmentioning
confidence: 99%